2020
DOI: 10.1007/s00894-020-4290-2
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of electronic, magnetic, elastic, mechanical, thermodynamic, and thermoelectronic properties of Mn2PtV Heusler alloy: ab initio study

Abstract: In this paper, we report electronic, magnetic, mechanical thermodynamic, and thermoelectric properties of Mn 2 PtV using density functional theory. Generalized gradient approximation (GGA) and GGA + U, where U is Hubbard correlation, have been set forth to examine the material for various properties. The material was found to have cubic Fm-3m (225) as the stable ground state. The investigated electronic results within GGA and GGA + U both present metallic nature for the compound. The calculated magnetic moment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 52 publications
4
7
0
Order By: Relevance
“…For the present case, using Equation ), its value is 0.19 (near to 0.25) reflecting the ionic bonding in the material. The extensive studies have been reported in the literature 32,48,53,64,67‐71 on similar kind of full HAs and our results follow them, reasonably.…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…For the present case, using Equation ), its value is 0.19 (near to 0.25) reflecting the ionic bonding in the material. The extensive studies have been reported in the literature 32,48,53,64,67‐71 on similar kind of full HAs and our results follow them, reasonably.…”
Section: Resultssupporting
confidence: 90%
“…Then other Mn‐based HAs such as Mn 2 CoAs, 62 Mn 2 TiZ ( Z = Al, As, Bi, Ga, Ge, Sb, Si, Sn), 63 Mn 2 ZrZ ( Z = Si, Ge), 64 Mn 2 ZnGe 65 and very recently in Mn 2 CoAl, 66 Mn 2 CoX, 67 Mn 2 ScZ ( Z = Si, Ge, Sn) 68 have been investigated and half‐metallic behaviour has been reported. In the same way, metallic behaviour has also been reported in Mn 2 PtV, 69 Mn 2 PtX ( X = Rh, Pd) 70 and Mn 2 CoCr 71 full HAs.…”
Section: Introductionsupporting
confidence: 67%
See 1 more Smart Citation
“…If the crystal is anharmonic, the phonon frequencies are volume‐dependent, and the thermal expansion coefficient is non‐zero at all temperatures. In this work, the γ value is also calculated from the following relationship between phonon frequencies (Debye temperature) and volume 67 : γ=dlnΘD()VdlnV. …”
Section: Resultsmentioning
confidence: 99%
“…In order to obtain the precise energy corresponding to the experimental reaction solvent system, we used a larger basis set to recalculate the single-point energy of all optimized geometries in the corresponding experimental solvents. This is also a widely used method to obtain accurate energy in catalytic reactions [30][31][32][33][34]. The larger basis set of 6-311 + + G (d, p) (SDD with ECP for Au) in the SMD implicit solvent environment [35] with acetonitrile (solvent = CH 3 CN, ε = 35.688) is used.…”
Section: Computational Detailsmentioning
confidence: 99%